INTERNALISASI ASUMSI PEMBELAJARAN ANDRAGOGI PADA MATA KULIAH STATISTIK - Elizon Nainggolan; Silvia Mariah; Fauzi Kurniawan (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
This type of research is a quasi-experimental research with pretest-posttest control group design that aims to determine differences in students' learning ability by using andragogy approach and learning by pedagogy approach. Population in this study all students Department of PLS NIM 2015. Sampling is done randomly after given treatment In each class. Data collected through documentation, test, and observation method. Based on the result of t test on pre-test, it was known that the average value obtained by the students in the experimental group is 75.23, which means higher than the average value in the control group that is 72.50. In t test we got tcount = -2,688; Whereas ttable, namely tdf = 29; ∝= 0,05 = 2.04. This means that tcount > tdf = 29; ∝= 0.05. So the pre-test is quite different although less significant. In the post test, it can be seen that the average value of students in the experimental group is 89.50 higher than the average score of the students in the control group is 77.00. In t test we got statistical value tcount = -10.012; Whereas ttable, namely tdf = 29; ∝ = 0.05 = 2.04; Which means that tcount> tdf = 29; ∝ = 0.05. So, the two average values are significantly different significantly. Based on the results of statistical tests it is known that: (1) the learning results seen from the average score of student exam results in following the learning by using andragogy approach significantly higher than the students who Follow the learning by using Pedagogical approach, (2) there is improvement of numeracy ability and data processing of student which can be seen from study result and average value in student group that follow learning by using approach of andragogy higher than student group that follow learning by using approach Pedagogy. Kata Kunci: Internalisasi, Andragogi, Pedagogi